The Right to Disconnect in the Context of Employees’ Mental Health - Dolobáč, Marcel; Skolodová, Katarína (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2022)
The development of technology has a significant impact and creates new requirements in the field of labour-law relations. One of these requirements is the protection of occupational health and safety by preventing the blurring of boundaries between employees’ work and private lives. The most important means which is currently the subject of discussions in the professional community, but also in practice, is the right to disconnect. This paper is devoted exactly to this right, its perception at the level of the institutions of the European Union, and its legal enshrinement in the legislation of the Slovak Republic.